![image](https://tex.z-dn.net/?f=%5Csin%283x-%5Cfrac%7B%5Cpi%7D%7B6%7D%29%3D%5Cfrac%7B1%7D%7B2%7D%3B%5C%5C%0A3x-%5Cfrac%5Cpi6%3D%28-1%29%5En%5Carcsin%5Cfrac12%2B%5Cpi+n.+n%5Cin+Z%5C%5C%0A3x-%5Cfrac%5Cpi6%3D%28-1%29%5En%5Cfrac%7B%5Cpi%7D%7B6%7D%2B%5Cpi+n%2C+n%5Cin+Z%5C%5C%0A3x%3D%5Cfrac%5Cpi6%281%2B%28-1%29%5En%29%2B%5Cpi+n%2C+n%5Cin+Z%5C%5C%0Ax%3D%5Cfrac%7B%5Cpi%7D%7B18%7D%281%2B%28-1%29%5En%29%2B%5Cfrac%7B%5Cpi+n%7D%7B3%7D%2C+n%5Cin+Z%5C%5C%0A+%5Cleft%5B+%7B%7Bx%3D%5Cfrac%7B%5Cpi%7D%7B9%7D%2B%5Cfrac%7B%5Cpi+n%7D%7B3%7D%2C%5C+n%3D2k%3D%3D%3Ex%3D%5Cfrac%5Cpi9%2B%5Cfrac%7B2%5Cpi+k%7D%7B3%7D%7D+%5Catop+%7Bx%3D%5Cfrac%7B%5Cpi+n%7D%7B3%7D%2C+%5C+n%3D2k%2B1%3D%3D%3E%5C+x%3D%5Cfrac%5Cpi3%2B%5Cfrac%7B2%5Cpi+k%7D%7B3%7D%7D%7D+%5Cright.+%0Ax%5Cin%5B-2%5Cpi%3B%5Cpi%5D%5C%5C+%0Ak%3D-3%3Ax%3D%5Cfrac%7B%5Cpi%7D%7B9%7D-2%5Cpi%3D-%5Cfrac%7B17%5Cpi%7D%7B9%7D%3B%5C+%5C+x%3D%5Cfrac%7B%5Cpi%7D%7B3%7D-2%5Cpi%3D-%5Cfrac%7B5%5Cpi%7D%7B3%7D%3B%5C%5C+)
x=\frac\pi9+\frac{2\pi k}{3}} \atop {x=\frac{\pi n}{3}, \ n=2k+1==>\ x=\frac\pi3+\frac{2\pi k}{3}}} \right.
x\in[-2\pi;\pi]\\
k=-3:x=\frac{\pi}{9}-2\pi=-\frac{17\pi}{9};\ \ x=\frac{\pi}{3}-2\pi=-\frac{5\pi}{3};\\ " alt="\sin(3x-\frac{\pi}{6})=\frac{1}{2};\\
3x-\frac\pi6=(-1)^n\arcsin\frac12+\pi n. n\in Z\\
3x-\frac\pi6=(-1)^n\frac{\pi}{6}+\pi n, n\in Z\\
3x=\frac\pi6(1+(-1)^n)+\pi n, n\in Z\\
x=\frac{\pi}{18}(1+(-1)^n)+\frac{\pi n}{3}, n\in Z\\
\left[ {{x=\frac{\pi}{9}+\frac{\pi n}{3},\ n=2k==>x=\frac\pi9+\frac{2\pi k}{3}} \atop {x=\frac{\pi n}{3}, \ n=2k+1==>\ x=\frac\pi3+\frac{2\pi k}{3}}} \right.
x\in[-2\pi;\pi]\\
k=-3:x=\frac{\pi}{9}-2\pi=-\frac{17\pi}{9};\ \ x=\frac{\pi}{3}-2\pi=-\frac{5\pi}{3};\\ " align="absmiddle" class="latex-formula">
значит имеем такие решения